Формування інноваційної моделі розвитку національної економіки - Васільєва, Леся Миколаївна; Vasilieva, Lesya (Дніпровський державний аграрно-економічний університет, 2016)
Визначено, що активізація інноваційної складової економічного розвитку вимагає формування моделі інноваційного розвитку. Встановлено тенденції та проаналізовано джерела фінансування інноваційної діяльності підприємств України. Сформульовано низку заходів щодо переведення національної економіки на інноваційну модель розвитку, спрямованих на приведення системи державного управління у модель економічного зростання. It was determined that the activation of the innovation component of economic development requires the formation of an innovative model of development. Trends innovation of recent years indicate that there are significant problems and a low level of development of innovative activity inUkraine. In most countries, budgetary funds are the main source of funding for innovation,Ukraineis characterized by a very different approach with minimal state participation. Formulated a series of measures to put the national economy on the innovative development model, aimed at bringing the public administration in the economic growth model, namely, the concentration in one state innovation process management body; improving the investment policy mechanisms, the direction of public funds for long-term research and innovation capabilities with self-sufficiency in the short term; the formation of innovative infrastructure development with an effective institutional support of innovative processes; creation of a state of stimulation of innovative activity of economic entities mechanisms; improving the legal framework for the development of innovation and investment processes; dissemination of innovative international cooperation.
Formation of innovative model of development of the national economy
Keywords: державне управління; public administration; інновації; innovations; модель; model; національна економіка; national economy; розвиток; development